Kontribusi Kompetensi Pedagogik dan Motivasi Kerja terhadap Kinerja Mengajar Guru - Eko Setiawan (Universitas Al-Hikmah Indonesia, 2018)
Teachers are required to have a teaching performance that can improve the quality of education. To achieve the quality of good education and quality, highly influenced teacher's teaching performance in carrying out its duties, so that teacher teaching performance becomes an important demand for educational success. This study reveals about the magnitude of the contribution of pedagogic competence and work motivation to the teaching performance of teachers. This research was conducted on kindergarten teacher Aisyiyah Se Bandung City by way of test to the teacher and spread the questionnaire to 54 kindergarten teacher Aisyiyah in Bandung City. The research findings show that pedagogic competence contribute to teacher's teaching performance of 19.09%. While work motivation contribute to teacher teaching performance of 27.98%. The pedagogic competence and work motivation simultaneously (simultaneously) the contribution to teacher teaching performance of 30.25%. Teachers need to demonstrate better teaching performance by working to improve their pedagogical skills and work motivation in order to improve the quality of education. While the foundation should pay more attention to the role of the teacher, because the task of the teacher is not an easy task. It needs to be appreciated to teachers, so that teachers are more focused and concentrate in their work as professional teachers.